Predictors of varying levels of risks posed by fixated individuals to British public figures. Issue 4 (21st March 2021) - Gill, Paul; Corner, Emily; Farnham, Frank; Wilson, Simon; Marchment, Zoe; Taylor, Alice; Taylor, Richard; James, David
Abstract: Concerning approaches and communications to the Royal Family and other British public figures are relatively numerous. This paper examines over 2000 such cases logged over a three‐year period in the United Kingdom. Using police and health data, the paper conducts a series of bivariate and multivariate analyses to demonstrate the predictors of what types of risk are posed by an individual case (e.g., communicate only, approach, security breach). The results showed that (a) the rates of serious mental disorders are higher among this sample than the general population base rate, (b) approachers were significantly more likely than communicators to suffer from serious mental disorders, (c) approachers were significantly more likely than communicators to have a history of substance use and abuse problems, (d) approachers were significantly more likely than communicators to have a history of violent behavior against property and persons, and (e) the motivations of approachers and communicators significantly differ. The paper concludes with a consideration of the implications for threat assessment and management.